Conceptions about the divine in Lisímaco Chavarría and Jorge Luis Borges: From the universe to the multiverse - Arley Fonseca, Mauricio (2021)
This article start off from a comparative interest about divines conceptions, and it takes as reference two autors Lisímaco Chavarría and Jorge Luis Borges, which literary texts converge with similar ideas, and one of those originates this work proposal: God as fountain of the transcendent. This drives to the main theoretical deliberation about the multivers, with its many faces of the divine existence. The sample of literary texts is compose by poems, tales and essays, wich Will be analyze according to theoretical inputs from Hermeneutics, Theology and Literature. In the development, God Will be expose with many faces, and manifested through nature, feminine, Aleph…, and in that way reach to many minds. But it is necessary to delimit that, in selected texts predominates a God of Jewish and Christian tradition, with some references to egyptian, mayas, incas and nordics divinities.